Scaling the number of plants per plot and number of plots per genotype of yellow passion fruit plants - doi: 10.4025/actasciagron.v36i1.17697 - Storck, Lindolfo; Lúcio, Alessandro Dal’Col; Krause, Willian; Araújo, Dejânia Vieira de; Silva, Celice Alexandre (Acta Scientiarum. Agronomy, 2014)
There is a demand for research on yellow passion fruit plants (Passiflora edulis Sims) used for juice production. Thus, the present study aimed to determine the number of plants per experimental plot and the number of plots per genotype for different properties of passion fruit. The data used were obtained from an experiment (Tangará da Serra, Mato Grosso State, Brazil) that assessed 13 fruit properties in eight genotypes of yellow passion fruit plants, with 10 replicates and 10 plants per plot. For each of the 80 experimental plots, the optimum plot size (Xo) was estimated by the method of maximum curvature of the coefficient of variation model. The number of replicates for each genotype and the means were estimated through the use of 10 plants per plot, combined with Xo plants per plot. The optimum plot size for the assessment of properties in yellow passion fruits independent of genotype is less than five plants, as the number of replicates is a function of the desired magnitude of accuracy. The number of plants per experiment is lower when using Xo plants per plot.